The acute haemodynamic response with endocardial biventricular pacing: comparing RV paced and LBBB patients. (19th May 2022) - Cantor, E; Butcher, C; Chow, JJ; Sohaib, S M A; Valli, H; Shun-Shin, M; Shi, R; Boyalla, V; O'connor, M; Chen, Z; Haldar, S; Mason, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boston Scientific Background: A third of patients that receive cardiac resynchronisation (CRT) are non-responders. Predictors of positive response include broader QRS duration, non-ischaemic aetiology and sinus rhythm, but it is still unclear whether lead placement site determines a positive responder. Purpose: We assessed the acute haemodynamic response of endocardial biventricular pacing in patients with intrinsic left bundle brunch block (LBBB) versus LBBB due to pre-existing right ventricular pacing (RVP). Methods: Patients who fulfilled standard criteria for CRT implantation but had failed conventional (coronary sinus) left ventricular (LV) lead placement (primary or revision) or were deemed clinical 'non-responders after > 6 months of conventional CRT were enrolled. The acute haemodynamic response during endocardial biventricular pacing was assessed with a roving LV lead at 9 different locations (basal and mid: septal, anterior, posterior and lateral walls and apex). Acute changes in beat-to-beat systolic blood pressure (SBP) in the left ventricle were recorded and analysed. Results: We recruited 23 patients across 10 UK centres: 14 intrinsic LBBB and 9 dependent on RVP. Patient characteristics were comparable: age (mean 67 + 10.6 years vs. 62 + 15.4 years), ischaemic (63% vs 50%), QRS (160 + 18ms vs. 190 + 36ms, p =0.07). Of the RVP group 5/9 had septal RV leads (the remainder apically positioned). There was no difference in the SBP improvement between the groups: change in SBP ranged from -5.25 – 19.91mmHg (median 3mmHg) in RVP patients vs -5.92 – 23.03mmHg (median 3mmHg) for intrinsic LBBB. However, the improvement in SBP was more consistent across the different segments in the patients with RVP (group A), as compared to intrinsic LBBB (group B), where the lateral wall and then non-septal walls provided the greatest haemodynamic improvement. Figure 1: depicts SBP improvement (in mmHg) during endocardial biventricular pacing in different positions within the LV for patients with RVP (A) vs underlying intrinsic LBBB (B): 9 segment model of the LV: Ant (anterior wall), Lat (lateral wall), Post (posterior wall), Sept (septum). Outer ring represents the four basal LV locations, middle ring the mid LV locations and centre ring the apex. Scale depicts mmHg improvement in SBP. Conclusion: When implanting an LV lead for patients who are RV pacing dependent any position within the LV provides an acute haemodynamic improvement, compared with those with intrinsic LBBB, where a targeted lateral wall approach is more important. This finding corroborates the key differences in LV activation patterns for induced versus intrinsic LBBB.